UPLC-ESI-QTOF-MS2-Based Identification and Antioxidant Activity Assessment of Phenolic Compounds from Red Corn Cob (Zea mays L.) - Hernández, María; Ventura, Janeth; Castro, Cecilia; Boone, Víctor; Rojas, Romeo; Ascacio Valdés, Juan; Martínez Ávila, Guillermo Cristian Guadalupe (2018)
Abstract: In this study, the extraction of phenolic antioxidants from red corn cob was carried out usingultrasound-assistedextraction(UAE).Thesolid:liquidratioandextractiontimewereevaluated when obtaining these bioactive compounds. The total phenolic contents were evaluated using the Folin Ciocalteu method, while the antioxidant activity was measured by ABTS•+ and DPPH• assays. The amount of phenolic compounds ranged from 215.17±33.49 to 527.33±103.79 GAE mg/100 g and, overall, high solid:liquid ratios and time periods release more phenolic compounds. Moreover, theredcorncobextractsshowedhigherradicalscavengingcapacityaccordingtotheresultsobtained usingtheABTS•+ techniquecomparedtotheDPPH• test. Thecouplingofliquidchromatographyand mass spectrometry assay allowed the determination of 11 phenolic compounds, including phenolic acidsandﬂavonoids. Thus,ourresultsdemonstratedfortheﬁrsttimethepotentialofredcorncobas asourceofbioactivecompounds,whichmightbeincludedinfoodandpharmacologicalpreparations. Keywords: phenols compounds; red corn cob; ultrasonic-assisted extraction; UPLC-MS2